STUDENTS’ ERROR ANALYIS IN FORMING PASSIVE SENTENCES BY USING INDIRECT AND DIRECT OBJECTS OF STKIP YPM ACADEMIC YEAR 2020/2021 - Elmaida S.Pd.I M.Pd; Fanalisa Elfa (INOVISH JOURNAL, 2021)
This  research  studies  about  the  students’  error  in  forming passive   sentences by using direct and indirect objects  at  the  English  Department  students  STKIP  YPM Bangko. The purpose o f this research was to find out the students’ error in forming passive sentences at the fourth semester STKIP YPM Bangko. This research was descriptive qualitative method. The population was 26 students at fourth semester on English Department STKIP YPM Bangko. They were selected as the sample by using total sampling technique. The data was collected by using writing test on passive sentences.  The finding showed that students’ errors in forming passive sentences were high in determining objects.Keywords: Indirect and Direct Objects, Passive Sentences